A quantitative morphometric study of the human anterior cingulate cortex. - Gittins, R; Harrison, P (2004)
Morphometric alterations in the anterior cingulate cortex (ACC) have been reported in schizophrenia and mood disorders. Parameters affected include glial and neuronal density, neuronal size and cortical thickness. Some data, especially in mood disorders, suggest that the left subgenual ACC is preferentially involved. Qualitative studies show that the ACC cytoarchitecture is heterogeneous, but there are few quantitative data. We performed a quantitative morphometric study of five anatomical levels within the ACC (caudal and rostral subgenual [area 24b sg], rostral and intermediate supragenual [area 24b] and caudal supragenual [area 24b']) in both hemispheres of five normal brains. We measured cortical depth, layer depths, neuronal density, neuronal size, and glial density, using the optical disector and nucleator. Relative to the subgenual ACC, the supragenual ACC was thicker, with a deeper layer V. Supragenual neurons were substantially larger in all layers, and were less densely packed in layers V and VI, than subgenual neurons. Glial density, and the glia to neuron ratio, was higher in supragenual than subgenual ACC. Only minor differences were seen between left and right ACC, between caudal and rostral subgenual ACC, and between the three supragenual levels. These data complement the qualitative descriptions of the heterogeneity of human ACC cytoarchitecture, connections, and functions, especially between supragenual and subgenual regions. Our findings also indicate that care must be taken when selecting ACC tissue to be used for morphometric studies of psychiatric disorders, since the normal anatomical variation is of a similar magnitude as the reported disease-related alterations.